Our mutual friend - Dickens, Charles, 1812-1870. (London, Aldine Press, 1907)
A satiric masterpiece about the allure and peril of money, "Our Mutual Friend" revolves around the inheritance of a dust-heap where the rich throw their trash. When the body of John Harmon, the dust-heap's expected heir, is found in the Thames, fortunes change hands surprisingly, raising to new heights "Noddy" Boffin, a low-born but kindly clerk who becomes "the Golden Dustman." Charles Dickens's last complete novel, "Our Mutual Friend" encompasses the great themes of his earlier works: the pretensions of the nouveaux riches, the ingenuousness of the aspiring poor, and the unfailing power of wealth to corrupt all who crave it. With its flavorful cast of characters and numerous subplots, "Our Mutual Friend" is one of Dickens's most complex--and satisfying--novels.
Keywords: Inheritance and succession -- Fiction; Social classes -- Fiction; Poor families -- Fiction; Deception -- Fiction; London (England) -- Fiction; Love stories; Satire